PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA (STUDI KASUS DESA PEKAN HERAN KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU TAHUN 2014) - Randa, Haricha Dwi; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Participation or involvement society in politics are the form of democracy in a country, the one of that democracy is a Musrenbang from the village to the national level. Musrenbang would be successful if all the delegation of society involve to participate and the process of implementation could be appropriate as Musrenbang principle in Kepmendagri No.050-187 / Kep / Bangda / 2007, there are equality, discussion, alignments, anti-domination, anti-discrimination, development village holistically. This research aims to investigate the implementation of Village Musrenbang in Pekan Heran Village already appropriate of the principles in Kepmendagri Musrenbang No.050-187 / Kep / Bangda / 2007.This research is a qualitative research is conducted with a descriptive approach. The technique of this research is using purposive sampling with 14 informants. The methods of data collection using interview techniques, and documentation.The technique of the data analysis is using triangulation.Based on the research results of the stages of the implementation of the Village Musrenbang Pekan Heran in 2014 is an appropriate conformity with as established, but a society participation in the activities of the Village Musrenbang low levels, because a society lack of education, social and economic, as well as the lack of socialization of village appliance, and the process of implementation Musrenbang Pekan Heran Village in 2014 is in appropriate yet with the principles Musrenbang in Kepmendagri No.050-187 / Kep / Bangda / 2007 in the principle of anti-domination, and holistic development.Keywords: Rural planning, Participate of Society, and Musrembang